Evaluation of Antifungal and Antibacterial Activities of the Plant Coccinia grandis (L.) Voigt. (Family- Cucurbitaceae) - Pinaki Pal, Subrata Chakraborty, Amalesh Samanta*, Bolay Bhattacharya, Monisankar Samanta (Journal of Phytology, 2010)
Coccinia grandis, family-Cucurbitaceae, a perennial tendril climber plant, possessing significant antidiabetic property. Other plants in the family Cucurbitaceae possessing diuretic, aphrodisiac, bitter stomachic, purgative and emetic properties. But antimicrobial activity of C. grandis has not been evaluated extensively. We have paid more importance on antimicrobial activities against various fungal strains and different gram positive and gram negative bacteria. Aqueous and ethanolic extract were used to evaluate antifungal and antibacterial activities. Antifungal activity was observed on Candida albicans and Aspergillus niger and antibacterial activity was observed on gram positive bacteria like Bacillus subtilis UC564, Bacillus pumilus-8241, Enterococcus faecalis ATCC-29212, Bacillus licheniformis, Staphylococcus aureus ATCC6571, StreptococcusÂ faecalis-52 and gram negative bacteria like Shigella boydii-Type12, Shigella flexneri E03429, Shigella dysenteriae-3 , Pseudomonas aeruginosa , Escherichia coli-K88, Salmonella typhi-62 , Salmonella choleraesuis-36 , Shigella boydii-8, Shigella flexneri NICED, Shigella sonnei E08869. Key words: Coccinia grandis, MIC, antifungal and antibacterial activities <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Bolay Bhattacharya et al. Evaluation of Antifungal and Antibacterial Activities of the Plant Coccinia grandis (L.) Voigt. (Family- Cucurbitaceae). Â J Phytol 2/11 (2010) 52-57